Aporte de las redes sociales como herramienta de la enseñanza y aprendizaje en los estudiantes de básica media de la Unidad Educativa Dr. Isidro Ayora Cueva del cantón Ventanas año 2022 - Monserrate Pacheco, Jorell Alexander (2022)
The general objective of this research was to determine the influence of social networks as a teaching and learning tool in elementary school students of the Isidro Ayora Cueva Educational Unit of the Ventanas canton, year 2021. The present study will be carried out using the research methodology with the descriptive, exploratory and explanatory types. Based on the objectives of the research, the combination of quantitative and qualitative data collection techniques was used. Through this research it was concluded that: Social networks are a very useful tool in educational life but also pose a great danger for adolescents, and can cause different diseases and disorders derived from their misuse. Also, comment that the most useful are those networks related to a specific topic and whose community is closed sharing a common interest.